Pattern of Pelvic Fractures, Associated Injuries and Early Complications in Patients Presenting to a Trauma Centre - Raja Umar Liaqat, Raja Umar Liaqat; Raja Umar Liaqat , Abeer Makhmoor , Rida Qasim Awan , Riaz Ahmed , Abdul Jabbar , Talia Urooj , Raja Umar Liaqat , Abeer Makhmoor , Rida Qasim Awan , Riaz Ahmed , Abdul Jabbar , Talia Urooj (Journal of Rawalpindi Medical College, 2019)
Background: To determine the frequency, pattern, associated injuries and early complications of pelvic fractures in patients presenting to a trauma centre. Methods: This prospective, cross-sectional study was done at the Department of Orthopaedics, Benazir Bhutto Hospital, Rawalpindi, Pakistan. The study involved patients aged 18 years and above admitted in the Orthopaedic department with pelvic fractures. The patients were managed according to Advanced Trauma Life Support (ATLS) protocol, and after stabilization, were followed up for a period of 3 weeks to look for any complications. This was done on day 1, 7, 14 and 21. Pelvic fractures were classified using Antero-posterior (AP), In-let and Out-let pelvic views, and all associated injuries were documented. Data was analyzed using SPSS version 22. Results: The study found that majority of patients with pelvic fractures were male (78%) with a mean age of 35.7±10.3 years. The average time before initiation of ATLS was 54.2±106.2 minutes. The main mechanism of injury was motor vehicle accidents (58%). The main Tiles fracture type was type B (68%). Head injury (22%) followed by genito-urinary injuries (16%) were the most common associated injuries. Conclusion: Associated injuries remain a challenge to the management of patients with pelvic fractures. Motor vehicle accidents were the major cause of pelvic fractures. Keywords: Advanced Trauma Life Support, Hemorrhagic shock, Pelvic fractures, Tiles classification.